2010
DOI: 10.1111/j.1523-536x.2010.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Depressive Symptoms and Preterm Birth: A Prospective Study of a Swedish National Sample

Abstract: Pregnant women reporting antenatal depressive symptoms are at elevated risk of preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 40 publications
2
48
1
Order By: Relevance
“…This cut-off score has been used previously in non-English-speaking pregnant women, including immigrants, 30 and was recently found to be associated with increased risk for preterm birth in a nonimmigrant sample. 31 SLEs were assessed with the CRISYS-R, a 63-item instrument that examines the occurrence of SLEs in the previous 6 months. The CRISYS-R was designed for use in a low-income, urban population and therefore captures many SLEs pertinent to the immigrant experience.…”
Section: Demographics and Psychosocial Assessmentmentioning
confidence: 99%
“…This cut-off score has been used previously in non-English-speaking pregnant women, including immigrants, 30 and was recently found to be associated with increased risk for preterm birth in a nonimmigrant sample. 31 SLEs were assessed with the CRISYS-R, a 63-item instrument that examines the occurrence of SLEs in the previous 6 months. The CRISYS-R was designed for use in a low-income, urban population and therefore captures many SLEs pertinent to the immigrant experience.…”
Section: Demographics and Psychosocial Assessmentmentioning
confidence: 99%
“…In particular, antenatal anxiety and depression are associated with preterm birth (Orr et al, 2007;Fransson et al, 2011) and have adverse implications for fetal neurodevelopment (Kinsella and Monk, 2009) and child outcomes (Conde et al, 2010;Alder et al, 2007). Beyond that, studies have shown that antenatal anxiety and depression are risk factors for postnatal depression (Milgrom et al, 2008); Yonkers et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Women with antenatal depression are at risk for interpersonal isolation and suicide, are less likely to receive adequate nutrition and obstetrical care, and are more likely to engage in smoking and substance abuse (Marcus and Heringhausen, 2009;Zuckerman et al, 1989). In infants, active depressive symptoms during pregnancy are associated with shorter length of gestation, restricted fetal growth, and lower birth weight (Davalos et al, 2012;Fransson et al, 2011;Grote et al, 2010). Gestational depression is one of the strongest predictors of postpartum depression (Dietz et al, 2007;Gaynes et al, 2005;Milgrom et al, 2008), which is associated with decreased maternal sensitivity and attachment (Campbell et al, 2004;Lindahl et al, 2005;McLearn et al, 2006;Paulson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%